2014
DOI: 10.1097/mbp.0000000000000055
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dipper/nondipper blood pressure patterns on global left ventricular systolic function in hypertensive diabetic patients

Abstract: This study shows that the nondipper pattern is associated with subclinical LV systolic dysfunction in treated hypertensive diabetic patients with preserved left ventricular ejection fraction. Also, elevated night-time SBP was found to be related to impaired LV systolic functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…Kalaycioglu et al . 22 found a significant reduction in GLS in nondippers compared with dippers in a sample of 86 treated hypertensive diabetic patients with a mean age of 57.8 years. They also reported night-time systolic BP to be associated independently with GLS and GLS rate in linear regression models adjusted for age, sex and LV mass index 22.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Kalaycioglu et al . 22 found a significant reduction in GLS in nondippers compared with dippers in a sample of 86 treated hypertensive diabetic patients with a mean age of 57.8 years. They also reported night-time systolic BP to be associated independently with GLS and GLS rate in linear regression models adjusted for age, sex and LV mass index 22.…”
Section: Discussionmentioning
confidence: 85%
“…22 found a significant reduction in GLS in nondippers compared with dippers in a sample of 86 treated hypertensive diabetic patients with a mean age of 57.8 years. They also reported night-time systolic BP to be associated independently with GLS and GLS rate in linear regression models adjusted for age, sex and LV mass index 22. In untreated hypertensive patients, Tadic et al 23 found reduced two-dimensional and three-dimensional LV GLS and reduced atrial longitudinal strain in nondippers compared with dippers.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…A módszertan lehetőséget teremt a falmozgászavarok kvantitatív jellemzésére, akár szubklinikus BK-i deformá-ciós eltérések korai detektálására (lásd még háromdimen-ziós STE) [26]. A 2DSTE alkalmas lehet bizonyos esetekben kezelések (például kemoterápia) BK-ra kifejtett hatásának, esetleges mellékhatásainak vizsgálatára, továbbkövetéses vizsgálatok elvégzésére [27].…”
Section: áBraunclassified